A STUDY ON THE EFFECTS OF NANO ALGINATE/CHITOSAN/LOVASTATIN ON LOCOMOTION, EXPLORATION AND RECOGNITION ACTIVITY IN OBESITY RAT MODEL - Nguyen Thi Hoa; Nguyen Le Chien; Can Van Mao (Tạp chí Y học Quân sự, 2026)
Objectives: To investigate the effects of nano-Alginate/Chitosan/Lovastatin on locomotor activity, exploratory behavior, and cognitive performance in a high-fat diet-induced obese rat model. Subjects and methods: An experimental, controlled, descriptive cross-sectional study on white male rats, including 30 rats (Group 1) fed a normal diet and 30 rats (Group 2) induced with obesity using a high-fat diet for 7 weeks. After 7 weeks, group 1 was randomly divided into 3 subgroups (1, 2, 3) and continued with a normal diet (group 1 received saline; group 2 received Lovastatin at a dose of 4 mg/kg; group 3 received nano Alginate/Chitosan/Lovastatin at a dose of 4 mg/kg) for 12 weeks; Group 2 was divided into 3 subgroups (4, 5, 6) and continued with a high-fat diet (group 4 received saline; group 5 received Lovastatin at a dose of 4 mg/kg; group 6 received nano Alginate/Chitosan/Lovastatin at a dose of 4 mg/kg) for 12 weeks. Rat behaviors were assessed after 12 weeks of intervention using the open-field and novel object recognition tests. Results: The locomotion of rats in the open-field: No significant differences were found among the experimental groups in total traveled distance, moved time within the open-field arena, or traveled distance in the central zone of the open field test. The exploration and recognition of rats in the object Recognition: There was a significant difference in the discrimination ratio to explore object between old and new objects of rats groups in groups 1, 2, 3 and 6. While no significant differences (p > 0.05) were observed in Groups 4 and 5. Conclusions: Nano Alginate/chitosan/Lovastatin improved locomotor activity, exploration and increased cognitive exploration and activity memory in obese rats fed a high-fat diet than in obese rats using Lovastatin alone and obese rats receiving NaCl.